Penegakan Hukum Keimigrasian Pada Kantor Imigrasi Kelas I TPI Jakarta Timur Berdasarkan Undang-Undang Keimigrasian dan Hukum Acara Pidana - Ayuningtyas Retnowati (Publikasi Indonesia, 2022)
Closely related to the increasing movement of people across borders in the era of globalization and free trade, migration has become a concern for countries in the world, including Indonesia. This is because every country has the sovereign right to regulate the traffic of people entering and leaving its territory. The movement of people in and out of a country's territory has various impacts, both beneficial and detrimental to the interests and lives of the people and the nation. In response to the aforementioned problems, in order to maintain the sovereignty of the state, protect the interests of the people and implement national law, the state has formulated laws and regulations relating to the regulation and supervision of the entry and exit of employees. In terms of immigration enforcement against foreigners living in Indonesia, this is related to sanctions for immigration violations, especially residence permits, which are realized in immigration administrative actions and criminal sanctions. The purpose of this study is to understand the situation of law enforcement in the field of immigration by the Immigration Department Category I TPI East Jakarta. Law No. 6 of 2011. Number 8 of 2021 concerning the Criminal Procedure Code.